Karakter Tokoh Candyland Sebagai Inspirasi Penciptaan Artwear - Asyifa, Naila Ummu; Suharno, Suharno; Marlianti, Mira (Mahesa Research Center, 2025)
The creation of this artwear was inspired by the iconic characters in the board game Candyland, namely Princess Lolly, Gramma Nutt, and Princess Frostine. The goal is to present the novelty of an expressive and innovative form of artwear through an experimental and conceptual design approach. The creation methods used are exploration, design, and realization. The creation method used to realize this artwear collection is exploration, design, and realization. The results of this creation research are three artworks that visually and conceptually represent the interpretation of the three characters in Candyland above. These three artwear pieces were presented at the West Java TVRI studio on April 30, 2025, with the title Bandung Fashion Runway, and aired on May 3, 2025